Representation of Power in Class Discourse: A Study of Communication Ethnography - Jumadi Jumadi (Universitas Negeri Malang, 2016)
This study is aimed at describing the use of power in class discourse covering representation of power in speech act, representation of power in communication patterns and function of power in class discourse. Communication ethnography and pragmatic methods were used. The research results show that the use of directive, assertive, and expressive acts in class discourse represent the power with certain domination; that the control of speech topics, interruptions, and overlapping tend to represent the power with certain domination that also effect the legitimacy of the user of this strategy. In relation to its function, power in class discourse is applied as a preventive, supportive, and corrective acts in order to achieve instructional objective.